Techno economic evaluation of cold energy from Malaysian liquefied natural gas regasification terminals - Majid, M.A.A. (MDPI AG, 2019)
In order to cater for increased demand for natural gas (NG) by the industry, Malaysia is required to import liquid natural gas (LNG). This is done through PETRONAS GAS Sdn Bhd. For LNG regasification, two regasification terminals have been set up, one in Sungai Udang Melaka (RGTSU) and another at Pengerang Johor (RGTPJ). RGTSU started operation in 2013 while RGTPJ began operation in 2017. The capacities of RGTSU and RGTPJ are 3.8 (500 mmscfd) and 3.5 (490 mmscfd) MTPA, respectively. RGTSU is an offshore plant and uses an intermediate-fluid-vaporization (IFV) process for regasification. RGTPJ is an onshore plant and employs open-rack vaporization (ORV). It is known that a substantial amount of cold energy is released during the regasification process. However, neither plant captures the cold energy released during regasification. This techno economic study serves to evaluate the technical and economic feasibility of the cold energy available during regasification. It was estimated that approximately 47,214 and 88,383 kWh of cold energy could be generated daily at RGTPJ and RGTSU, respectively, during regasification processes. Converting this energy into RTh at 70 thermal eficiency, and taking the commercial rate of 0.549 Sen per RTh, for the 20-year project life, an internal rate of return (IRR) of up to 33 and 17 was estimated for RGTPJ and for RGTSU, respectively. Â© 2019 MDPI AG. All rights reserved.